What every Christian needs to know about the Qur'an - White, James R. (James Robert), 1962- (Minneapolis, MN : Bethany House Publishers, 2013)
"Apologist uses the text of the Qur'an to explore the differences between Islam and Christianity"--Provided by publisher.
Introduction: why study the Qur'an? -- The Qur'an and Muhammad of Mecca -- The Qur'an: a brief introduction -- Allah: Tawhid, Shirk, the Mithaq and the Fitra -- Say not three: the Qur'an and the Trinity -- Jesus in the Qur'an -- The Qur'an and the cross -- The scales: salvation in the Qur'an -- Did the people of the book corrupt the Gospel? -- Prophecies of Muhammad in the Bible -- The perfection of the Qur'an: parallels and sources -- The perfection of the Qur'an: transmission and text.
Includes bibliographical references (pages 292-300) and index.
Keywords: Qurʼan -- Christian interpretations; Apologetics; Christianity and other religions -- Islam; Islam -- Relations -- Christianity